2019
DOI: 10.1167/iovs.18-25941
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary and Macular Vessel Density in Dysthyroid Optic Neuropathy: An Optical Coherence Tomography Angiography Study

Abstract: PURPOSE. To evaluate peripapillary and macular vessel density in eyes with dysthyroid optic neuropathy (DON) and its correlation with visual function. METHODS. Patients diagnosed as thyroid-associated ophthalmopathy (TAO) with or without DON and healthy participants were recruited. All subjects underwent a complete ophthalmic examination and optical coherence tomography angiography centered on the fovea and the optic nerve head. Microvascular measurements were summarized as vessel density in the whole image an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 26 publications
(33 reference statements)
9
50
1
5
Order By: Relevance
“…In the current study, we found that the RCDs in both the SRCL and DRCL of the two TAO groups were lower than in the controls. Similar results were also reported by Zhang et al [31] though they only detected the vascular density in the SRCL. In addition, we found that the RCDs in SRCL and the GCC thickness were positively correlated in the TAZ region and in the T, I, and N sectors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, we found that the RCDs in both the SRCL and DRCL of the two TAO groups were lower than in the controls. Similar results were also reported by Zhang et al [31] though they only detected the vascular density in the SRCL. In addition, we found that the RCDs in SRCL and the GCC thickness were positively correlated in the TAZ region and in the T, I, and N sectors.…”
Section: Discussionsupporting
confidence: 90%
“…We found that, in support of the speculation by Meirovitch et al [12], the thicknesses of the NFL, GCL + IPL, and GCC were all decreased in both TAO subgroups and are likely responsible for the thinning of the whole retina around the macula. Zhang et al [31] also reported similar decreases of the GCC layer thickness in the DON group. Mechanical compression of the retina by orbital contents, decreased blood supply, as well as secondary increases in IOP were considered as possible reasons for ganglion cell atrophy resulting in macular thinning in the eyes with TAO [12].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The damage to the optic nerve due to intraneural edema alters microvasculature and interruption of direct axoplasmic transport. Also, vascular insufficiency resulted from the altered microvasculature might be an important pathogenic mechanism in other optic neuropathies [20,23,24], which implies that the abnormal hemodynamic state participates in the course of ITON, and the decompression surgery is effective by improving the retinal vasculature alteration. The spectrophotometric retinal oximetry and the optical coherence tomography angiography (OCT-A) are both noninvasive diagnostic tools to evaluate hemodynamic changes in eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…e pathogenesis of DON includes multiple factors. Bulging of orbital connective tissue and fat leads to hypertrophy of extraocular muscle and obstruction of venous return which in turn induces high intraorbital pressure and decreased vessel density in the peripapillary area [5]. Orbital crowding may also result in increasing pressure in the episcleral veins, which may lead to increasing intraocular pressure (IOP) and optic nerve compression [6].…”
Section: Introductionmentioning
confidence: 99%